Version 3 of the National Alzheimer's Coordinating Center's Uniform Data Set. (October 2018) - Besser, Lilah; Kukull, Walter; Knopman, David S.; Chui, Helena; Galasko, Douglas; Weintraub, Sandra; Jicha, Gregory; Carlsson, Cynthia; Burns, Jeffrey; Quinn, Joseph; Sweet, Robert A.; Rascovsky, Katya; et al.
Abstract : Introduction: In 2015, the US Alzheimer's Disease Centers (ADC) implemented Version 3 of the Uniform Data Set (UDS). This paper describes the history of Version 3 development and the UDS data that are freely available to researchers. Methods: UDS Version 3 was developed after years of coordination between the National Institute on Aging-appointed Clinical Task Force (CTF), clinicians from ∼30 ADCs, and the National Alzheimer's Coordinating Center (NACC). The CTF recognized the need for updates to align with the state of the science in dementia research, while being flexible to the diverse needs and diseases studied at the ADCs. Version 3 also developed a nonproprietary neuropsychological battery. Results: This paper focuses on the substantial Version 3 changes to the UDS forms related to clinical diagnosis and characterization of clinical symptoms to match updated consensus-based diagnostic criteria. Between March 2015 and March 2018, 4820 participants were enrolled using UDS Version 3. Longitudinal data were available for 25, 337 of the 37, 568 total participants using all UDS versions. Discussion: The results from utilization of the UDS highlight the possibility for numerous research institutions to successfully collaborate, produce, and use standardized data collection instruments for over a decade. Abstract : Supplemental Digital Content is available in the text.